Synthesis of Gd2O3/Sm2O3 nanocomposite via sonication and hydrothermal methods and its optical properties. (January 2015) - Muneer, Iqra; Farrukh, Muhammad Akhyar; Javaid, Shaghraf; Shahid, Maryam; Khaleeq-ur-Rahman, Muhammad
Highlights: Synthesis of Gd2 O3 /Sm2 O3 nanocomposite by ultrasonic and hydrothermal methods. Comparison of particle size by using Scherrer and Wood-Tauc equations with TEM. Effect of sonication time on particle size was investigated. Effect of pH and sonication time on band gap was studied. Abstract: Gadolinium oxide–samarium oxide (Gd2 O3 /Sm2 O3 ) nanocomposite was synthesized via sonication and hydrothermal methods. The sample was characterized by using thermogravimetric analysis and Fourier transformation infrared spectroscopy. The average crystalline size was calculated by Scherrer equation, Wood–Tauc relation using X-ray diffraction and transmission electron microscope. The size was found to be in a range of 15–30 nm. The morphological study was carried out with scanning electron microscope. Optical properties were investigated by solid phase and UV–visible absorption spectrophotometer. The band gap energy of the Gadolinium oxide was shifted from 5.3 eV to 2.3 eV. The change in band gap indicates red shift in nanocomposite.